Implementasi Wireguard VPN di Mikrotik Untuk Pengembangan Akses Jarak Jauh Dengan Metode NDLC Pada PT Excellent Infotama Kreasindo - Muhammad Nugi Abdiansyah; Imam Farisi (PT. Hasba Edukasi Mandiri, 2025)
The rapid advancement of information technology has driven the need for secure and efficient network access solutions, particularly for companies that require remote connectivity. One such solution that has emerged is the use of modern VPN protocols, such as WireGuard, which offers faster speeds and better security compared to traditional VPN protocols. PT Excellent Infotama Kreasindo, a company engaged in the field of computerization and information technology, requires stable remote access to support its business operations. The implementation of WireGuard VPN on MikroTik devices using the Network Development Life Cycle (NDLC) method was carried out to enhance the performance of secure and efficient remote access.